Enhanced seismic hazard assessment and risk zoning in the Kashan Region, Central Iran: Insights from historical data and advanced modeling techniques - Ahmad Adib; Pooria Kianoush (Results in Earth Sciences)
This research focuses on earthquake risk zoning in the Kashan region of central Iran—an area with significant seismic activity due to its location along major fault lines. Central Iran is bordered to the east by the Lut Block, to the north by the Alborz mountain range, and to the south by the Sanandaj-Sirjan region, forming the Iranian plateau. The study area, located in Isfahan province approximately 100 kilometers from Kashan, lies within the structural zones of the elevated Zagros, Sanandaj-Sirjan, and the volcanic arc of Urmia-Dokhtar. The study aims to enhance understanding of seismic hazards and improve risk assessment methodologies. Key findings include the identification of historical earthquakes, which underscore the region's vulnerability. Advanced probabilistic seismic hazard assessment techniques were employed using the OpenQuake platform to model seismic risks effectively. This research is novel in its integration of historical data with modern probabilistic modeling, providing a comprehensive framework for assessing seismic hazards in an underexplored region. Results indicate that while some areas exhibit low seismic activity, the potential for future earthquakes remains significant, highlighting the need for updated hazard assessments. A critical finding is the extended intervals associated with major earthquakes, which may lead to an underestimation of seismic risk. Additionally, the analysis of fault systems reveals complex interactions that influence the seismic behavior of Kashan, providing insights for urban planning and disaster preparedness. Ultimately, this research aims to inform local authorities and stakeholders about seismic risks, enabling effective mitigation strategies and enhancing community resilience against potential disasters.